Phospholipase C2 Affects MAMP-Triggered Immunity by Modulating ROS Production. Issue 2 (21st August 2017) - D'Ambrosio, Juan Martín; Couto, Daniel; Fabro, Georgina; Scuffi, Denise; Lamattina, Lorenzo; Munnik, Teun; Andersson, Mats X.; Álvarez, María E.; Zipfel, Cyril; Laxalt, Ana M.
Abstract : Arabidopsis Phospholipase C2 (PLC2) participates in a branch of microbe-associated molecular pattern-triggered immunity that involves reactive oxygen species-regulated processes. Abstract: The activation of phosphoinositide-specific phospholipase C (PI-PLC) is one of the earliest responses triggered by the recognition of several microbe-associated molecular patterns (MAMP s) in plants. The Arabidopsis ( Arabidopsis thaliana ) PI-PLC gene family is composed of nine members. Previous studies suggested a role for PLC2 in MAMP -triggered immunity, as it is rapidly phosphorylated in vivo upon treatment with the bacterial MAMP flg22. Here, we analyzed the role of PLC2 in plant immunity using an artificial microRNA to silence PLC2 expression in Arabidopsis. We found that PLC2 -silenced plants are more susceptible to the type III secretion system-deficient bacterial strain Pseudomonas syringae pv tomato ( Pst ) DC3000 hrcC − and to the nonadapted pea ( Pisum sativum ) powdery mildew Erysiphe pisi . However, PLC2 -silenced plants display normal susceptibility to virulent ( Pst DC3000) and avirulent ( Pst DC3000 AvrRPM1) P. syringae strains, conserving typical hypersensitive response features. In response to flg22, PLC2 -silenced plants maintain wild-type mitogen-activated protein kinase activation and PHI1, WRKY33, and FRK1 immune marker gene expression but have reduced reactive oxygen species (ROS )-dependent responses such as callose deposition and stomatal closure. Accordingly, the generation of ROS upon flg22 treatment is compromised in the PLC2 -defficient plants, suggesting an effect of PLC2 in a branch of MAMP -triggered immunity and nonhost resistance that involves early ROS -regulated processes. Consistently, PLC2 associates with the NADPH oxidase RBOHD, suggesting its potential regulation by PLC2.